First Evidence of a Relationship Between Female Major Histocompatibility Complex Diversity and Eggshell Bacteria in House Sparrows (Passer domesticus) - Darolová, Alžbeta; Poláček, Miroslav; Krištofík, Ján; Lukasch, Barbara; Hoi, Herbert (Frontiers in Ecology and Evolution, 2021)
Bacteria are known to influence animals’ health and fitness. Those bacteria that inhabit the skin and organs of vertebrates, in particular, are a pool of horizontal and vertically transmitted bacteria, e.g., avian mothers can transfer bacterial strains to eggshells through the reproductive tract, therefore, the reduction of vertical transmission to protect host offspring, is an important issue. In this context the female immune system might play an important role in avoiding the vertical transmission of potentially pathogenic bacteria. Here we investigate the relationship between the major histocompatibility complex (MHC) and cultivable eggshell bacteria originating from the female urogenital tract, in a captive population of house sparrows (Passer domesticus). Hence, we predict that females with more variable MHC complex will transfer a smaller quantity of bacteria onto the eggshells. Our results show a negative relationship between the number of functional MHC alleles and bacteria that grow in a selective medium. This is, to date, the first study demonstrating the role of female MHC diversity on eggshell bacteria and hence, may suggest the potential influence of maternal MHC on hatching success and offspring survival.